1970
DOI: 10.3126/init.v4i0.5531
|View full text |Cite
|
Sign up to set email alerts
|

The Pack Hunter (Dhole): Received Little Scientific Attention

Abstract: Abstract:The dholes received little scientifi c attention due to the lower charisma factor than other larger carnivores found in the same areas like Tiger and Snow Leopard. Introduction:The dholes or Asiatic wild dogs (Cuon alpinus) are one of the least studied social carnivores in the world. Dhole range includes central and east Asia, from China (Manchuria) in the north to India and the Malay Peninsula in the South. They are also found on the islands of Sumatra and Java but are absent in Borneo, Srilanka a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…On several occasions, dholes also preyed on domesticated animals (sheep and cattle). The occurrence of many illegal herding practices in the park (Nurvianto et al, 2015b) facilitates this, as is also reported to occur in India (Cohen et al, 1978;Johnsingh, 1992;Selvan et al, 2013b;Srivathsa et al, 2014), Bhutan (Wang & Macdonald, 2009;Thinley et al, 2011), and Nepal (Khatiwada et al, 2011). The presence of domesticated ungulates inside the park, competitors for forage, is a cause of reduced body condition, reproductive rates, and survival of native ungulate species (Sundararaj et al, 2012).…”
Section: Predation On Domestic Livestockmentioning
confidence: 89%
See 2 more Smart Citations
“…On several occasions, dholes also preyed on domesticated animals (sheep and cattle). The occurrence of many illegal herding practices in the park (Nurvianto et al, 2015b) facilitates this, as is also reported to occur in India (Cohen et al, 1978;Johnsingh, 1992;Selvan et al, 2013b;Srivathsa et al, 2014), Bhutan (Wang & Macdonald, 2009;Thinley et al, 2011), and Nepal (Khatiwada et al, 2011). The presence of domesticated ungulates inside the park, competitors for forage, is a cause of reduced body condition, reproductive rates, and survival of native ungulate species (Sundararaj et al, 2012).…”
Section: Predation On Domestic Livestockmentioning
confidence: 89%
“…Consequences for conservation: The presence of herding activities in BNP provides alternative prey for dholes but at the same time it brings complications to the conservation situation for this wild dog. The dhole is known as an opportunistic hunter; preying on whatever animals they encounter (Khatiwada et al, 2011). On several occasions, dholes also preyed on domesticated animals (sheep and cattle).…”
Section: Predation On Domestic Livestockmentioning
confidence: 99%
See 1 more Smart Citation
“…India lost around 60% of Dholes in the last 100 years (Karanth et al 2010) and less than 1,500 individuals are left in Indian forests (Johnsingh & Acharya 2013;Kamler et al 2015), surviving majorly in Western and Eastern Ghats, Terai, Kumaon, Himalayan region, northeastern states, and relatively larger population in central India (Srivastava & Singh 2003;Durbin et al 2004;Iyengar et al 2005;Jhala et al 2008;Karanth et al 2009;Gopi et al 2010;Johnsingh & Acharya 2013;Kamler et al 2015). Although the population disappeared from former range (Johnsingh 1985;Kamler et al 2015), the recent rediscoveries in newer areas have raised the hope in Sikkim (Bashir et al 2014), western Himalaya (Pal et al 2018), Tso Kar, Ladakh (Kamler et al 2015), and in different parts of Nepal (Khatiwada et al 2011;Thapa et al 2013;Lamichhane et al 2018;Yadav et al 2019). These discoveries indicate that the species is moving out to ensure fewer competition and less disturbance, which in future may foster resilience and expand its range.…”
Section: Open Accessmentioning
confidence: 99%
“…Although deemed shy and elusive with infrequent interactions with humans (Srivathsa et al, 2020), this species has disappeared from ∼82% of their former range (Wolf and Ripple, 2017) through habitat loss and human persecution (Karanth et al, 2010). For example, dholes in India were deemed vermin and hunted to near extinction (Cohen, 1978), while in Nepal, dholes were poisoned and shot as pests (Khatiwada et al, 2011). Similarly, dholes in Bhutan were considered pests and subjected to mass poisoning in the 1970s and 1980s (Wang and Macdonald, 2006;Thinley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%